PELATIHAN SPEAKING SKILL PADA PENDIDIK (DOSEN) DI FAKULTAS KEPERAWATAN DENGAN METODE ROLE PLAY DI INSTITUT KESEHATAN MEDISTRA LUBUK PAKAM - SULASTRI BR GINTING; TEDTY ROHAYA TINAMBUNAN; NOVRIKA SILALAHI; HARIATI HARIATI; Sri Sudewi Pratiwi Sitio (Jurnal Pengabdian Masyarakat Putri Hijau, 2022)
This activity is one way to face globalization where the 4.0 industrial revolution and 5.0 Society era are known. In this era, the whole world uses English as the language of instruction. Educators (lecturers) with health backgrounds are also required to be able to communicate in English to become educators (lecturers) who go international such as be able to further study abroad an educator (lecturer) must master English both in TOEFL test and interviews. The other reason is some institutions at the doctoral level requiring a TOEFL test before attending lectures. In addition, campuses that can accept foreign students in terms of increasing study program accreditation must have educators (lecturers) who are fluent in English. From this explanation, we can conclude that English is very important, especially for nursing educators at Health Institute of Medistra Lubuk Pakam who send their students abroad to work. Therefore, this activity aims to improve speaking skills in English in Educators (Lecturers) who do not teach English are Nursing Educators (Lecturers) who will send their students to work abroad or even continue their studies abroad. By using the Role Play method "Health English Conversation" so that nursing educators (lecturers) can apply teaching in the classroom using English so that students are also motivated to master English and learning materials in the teaching and learning process are more interesting.